Analysis of Fintech Payment : Urban Vs Rural in Bangka - Fitari, Tiara; Oktariani, Dini (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
The aim of this research is to analyze how Fintech Payment is implemented in Urban and Rural communities in Bangka Belitung. The data collection technique used by researchers is a field survey by filling out questionnaires with respondents. The focus of this research is to analyze whether there are differences in the implementation of fintech payments in Bangka Belitung Urban and Rural. The test tool used was SPSS version 29.02 by carrying out different tests on two groups. Based on different tests carried out using the Mann Whitney Test, the researchers found that there were significant differences in the implementation of fintech payments between urban and rural communities due to several factors, namely convenience, satisfaction and security. The study shows that by knowing the obstacles that occur in using technology, we can implement policies so that the use of technology can be felt by the whole community and can also encourage economic growth in Bangka Belitung. The development of technology adoption can also occur not only in urban communities but also in rural with the support of various parties, for example companies, government, education and other parties